2011年考研数二第04题解析

题目

微分方程 $y^{”} – \lambda^{2}y = e^{\lambda x} + e^{- \lambda x} (\lambda > 0)$ 的特解形式为 $?$

$$
A. a (e^{\lambda x} + e^{- \lambda x})
$$

$$
B. ax (e^{\lambda x} + e^{- \lambda x})
$$

$$
C. x (ae^{\lambda x} + be^{- \lambda x})
$$

$$
D. x^{2} (ae^{\lambda x} + be^{- \lambda x})
$$

解析

首先,$y^{”} – \lambda^{2}y = 0$ 的特征方程为:

$$
\lambda^{2} – \lambda^{2} = 0 \Rightarrow
$$

$$
\lambda_{1} = \lambda;
$$

$$
\lambda_{2} = – \lambda.
$$

于是,对于 $y^{”} – \lambda^{2}y = e^{\lambda x}$ 而言,其特解为:

$$
y_{1}^{*} = ax e^{\lambda x}.
$$

对于 $y^{”} – \lambda^{2}y = e^{- \lambda x}$ 而言,其特解为:

$$
y_{2}^{*} = bx e^{- \lambda x}.
$$

于是,$y^{”} – \lambda^{2}y = e^{\lambda x} + e^{- \lambda x}$ 的特解为:

$$
y^{*} = y_{1}^{*} + y_{2}^{*} \Rightarrow
$$

$$
ax e^{\lambda x} + bx e^{- \lambda x} =
$$

$$
x (ae^{\lambda x} + be^{- \lambda x}).
$$

综上可知,正确选项为 $C$.